Perancangan Aplikasi Manajemen Akreditasi sebagai Layanan Peningkatan Mutu Institusi (Journal Innovations Computer Science, 2022)
The specific purpose of the research is to generate concepts and develop new models to assess higher education performance by referring to Study Program Accreditation (APS 4.0) and Institutional Accreditation (APT 3.0) BAN-PT which can monitor and evaluate quality performance, and document in accordance with accreditation instruments, as well as implement an intelligent system algorithm that is able to assess the quality of higher education performance. Broadly speaking, this research is divided into three stages of research, namely pre-development data collection, development and implementation, and post-development data collection. From the results of the distribution of questionnaires on the use of the application, it has been seen from the support and Universities that relatively positive needs are needed as applications to support the accreditation process. At the end of 2020, this application has been implemented for PT AMIK Indonesia's accreditation activities and the response from Assessors has been very good and this application can replace the use of Google Drive as a documentation medium in the accreditation assessment process. The use of the flutter framework supports attractive visualizations with a fast development process.